Multi-criteria decision-making method under the complex intuitionistic fuzzy environment - Bilal, Muhammad; Ul Haq, Inam; Kausar, Nasreen; Khan, Muhammad Ishfaq; Pamucar, Dragan; El Maalou, Joseph (INT SCIENTIFIC RESEARCH PUBLICATIONS, 2025)
Complex intuitionistic fuzzy sets, which are distinguished by both membership and non-membership values, provide sophisticated decision-making tools by helping decision-makers better handle ambiguity, reluctance, and uncertainty in complex situations. In this paper, we introduce several novel operations on complex intuitionistic fuzzy sets, including a complex intuitionistic fuzzy distance measure, which is utilized to define sigma-equalities of complex intuitionistic fuzzy sets. This method is applied to a decision-making scenario that takes place in the real world in order to show its practical value. This scenario illustrates the potential of complex intuitionistic fuzzy sets in tackling difficult and ambiguous choice issues with increased flexibility and accuracy. Finally, in order to demonstrate the efficacy of the suggested strategy, we compare it to other methods that have been taken in the past.
Keywords: Complex intuitionistic fuzzy set; operations on complex intuitionistic fuzzy set; decision-making matrices; decision-making method; DISTANCE MEASURE; SETS; Mathematics